Pengaruh Kualitas Layanan Perangkat Desa Dan Penanganan Keluhan Terhadap Kepuasan Masyarakat Desa Sei Suka Deras - Maya Citra (Journal on Education, 2023)
This study aims to determine the effect of village service quality and complaint handling on the satisfaction of the people of Sei Suka Deras Village. This type of research is quantitative descriptive and obtains data by distributing questionnaires to respondents who were sampled in this study and then the data is processed using SPSS (Statistical Product). and Service Solutions) version 25.00. This study used a sample of 98 respondents from the Sei Suka Deras Village community. The test tools used are instrument test and classical assumption test. From this study it can be concluded that based on the results of the analysis of hypothesis 1 is accepted, meaning that the Service Quality Variable (X1) has an effect on the Community Satisfaction Variable (Y). hypothesis 2 is accepted, meaning that the Complaint Handling Variable (X2) has an effect on the Community Satisfaction Variable (Y). hypothesis 3 is accepted, meaning that the Service Quality Variable (X1), and the Complaint Handling Variable (X2) have a simultaneous (simultaneous) effect on the Community Satisfaction Variable (Y).